Interferon-gamma and IL-5 associated cell-mediated immune responses to HPV16 E2 and E6 distinguish between persistent oral HPV16 infections and noninfected mucosa - Paaso Anna; Koskimaa Hanna-Mari; Welters Marij JP; Kero Katja; Rautava Jaana; Syrjänen Kari; van der Burg Sjoerd H; Syrjänen Stina (WILEY, 2022)
Objectives: Natural history of human papillomavirus (HPV) infection in the head and neck region is poorly understood, and their impact on collective HPV-specific immunity is not known.
Materials and methods: In this study, we have performed a systematic analysis of HPV16-specific cell-mediated immunity (CMI) in 21 women with known oral and genital HPV DNA status and HPV serology (Ab) based on 6-year follow-up data. These women being a subgroup from the Finnish Family HPV Study were recalled for blood sampling to be tested for their CMI-responses to HPV16 E2, E6, and E7 peptides.
Results: The results showed that HPV16 E2-specific lymphocyte proliferation was more prevalent in women who tested HPV16 DNA negative in oral mucosa and were either HPV16 seropositive or negative than in HPV16 DNA+/Ab+ women (p = 0.046 and p = 0.035). In addition, the HPV16 DNA-/Ab- women most often displayed E6-specific proliferation (p = 0.020). Proportional cytokine profiles indicated that oral HPV16-negative women were characterized by prominent IFN-gamma and IL-5 secretion not found in women with persisting oral HPV16 (p = 0.014 and p = 0.040, respectively).
Conclusions: Our results indicate that the naturally arising immune response induced by oral HPV infections displays a mixed Th1/Th2/Th17 cytokine profile while women with persisting oral HPV16 might have an impaired HPV16-specific CMI, shifted partly toward a Th2 profile, similarly as seen earlier among patients with high-grade genital HPV lesions. Thus, the lack of HPV 16 E2 and E6 specific T memory cells and Th2 cytokines might also predispose women for persistent oral HPV16 infection which might be related to the risk of cancer.